Evaluating the performance and feasibility of integrating thermoelectric generators with solar photovoltaic panels: A case study - D Lakshmi Satya Nagasri; ram kumar Alajingi; Ponnambalam Pathipooranam; S. Senthil raja; Mohd Faiz bin Mohd Salleh; R. Marimuthu (Case Studies in Thermal Engineering)
This case study explores the integration of thermoelectric generators (TEG) with solar photovoltaic (SPV) panels, aiming to reduce panel temperature, improve energy density, and decrease space requirements. A comparative experimental analysis between ideal PV, PV + TEG, and PV alone is conducted. A 445Wp SPV panel for all cases with 180 TEGs attached in PV + TEG mode is analyzed. Experimental results show that the hybrid PV + TEG system enhances power density by 8.5 % and reduces space needs by 16 % for the same power output. However, the integration increases the cost per unit by 25.12 % compared to PV panels alone, making it less economically feasible. Ideal PV panels demonstrated superior cost efficiency and power density. Despite the higher operational costs, the hybrid system is beneficial in space-constrained scenarios due to its higher energy density. Further, a conclusion is drawn from the techno-economic analysis to focus on optimizing the number of TEGs placed under SPV and improving MPPT algorithms to enhance performance and reduce costs.